2015
DOI: 10.1111/aogs.12831
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery pathways in abdominal gynecologic surgery: a systematic review and meta‐analysis

Abstract: The available evidence based on a broad range of non-randomized studies at high risk of bias suggests that enhanced recovery pathways may reduce length of postoperative hospital stay in abdominal gynecologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 68 publications
(142 reference statements)
8
54
0
9
Order By: Relevance
“…An important consistency among these trials, and shared with this retrospective cohort, is the mixed malignant and benign patient populations. A 2015 meta-analysis of the ERAS program in gynecology performed a subgroup analysis of length of stay according to patient pathology, which concluded that 'introduction of an ERAS pathway did not significantly affect length of stay in the study with a mixed (benign or malignant) patient group' 27. Another possible contributing factor is the lack of clearly defined minimal discharge criteria.…”
Section: Discussionmentioning
confidence: 99%
“…An important consistency among these trials, and shared with this retrospective cohort, is the mixed malignant and benign patient populations. A 2015 meta-analysis of the ERAS program in gynecology performed a subgroup analysis of length of stay according to patient pathology, which concluded that 'introduction of an ERAS pathway did not significantly affect length of stay in the study with a mixed (benign or malignant) patient group' 27. Another possible contributing factor is the lack of clearly defined minimal discharge criteria.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Initially, ERAS protocols were primarily instituted in the field of colorectal surgery, 6,7 emphasizing the beneficial use of preoperative medication, limited use of bowel preps, multimodal analgesia, intraoperative fluid restriction, prompt enteral nutrition, and early patient ambulation. 2,4,8Y10 Enhanced recovery after surgery regimens have been employed in gynecologic surgery 4,11 and in Europe, 1,12,13 but scarcely in the community hospital setting.…”
mentioning
confidence: 99%
“…We found a possible subsequent mobilization effect after patients' experienced harmony or disharmony between patients' interpretation of healthcare professional attitude and own experienced health state, but our data is not exhaustive in this regard. Early mobilization is regarded important (Bakhru et al, 2015) and is a common part of early recovery pathways after surgery (de Groot et al, 2016;Day et al, 2015). What affects early postoperative mobilization is multifactorial, which need further investigation, and our input might go some way to explain why tests of early mobilization programs give mixed results (Castelino et al, 2016).…”
Section: Discussionmentioning
confidence: 98%